UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI PUISI MELALUI STRATEGI TTW (THINK TALK WRITE) SISWA KELAS IV-B DI UPT. SD NEGERI 01 LIMO KAUM - Ratnawilis Ratnawilis (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
One of the teacher's efforts to improve student learning outcomes is to choose an appropriate learning model. One of them is the Think Talk Write (TTW) Strategy learning model, which is a learning model in which students work in groups and take turns explaining the material being studied. The objectives of this study were (1) To determine teacher activity using the Think Talk Write (TTW) Strategy learning model, (2) To determine student activities using the Think Talk Write Strategy (TTW), (3) To determine student learning outcomes with the Strategy. Think Talk Write (TTW) on poetry material for grade IV even semester. The subjects in this research were students of class IV-B UPT, SD Negeri 01 Limo Kaum for the 2019/2020 school year, which consisted of 26 students. This research uses classroom action research (PTK), data collected through (1) teacher observation sheets, (2) student observation sheets (3) test questions on student learning outcomes. The data analysis in this study used a percentage formula. Based on the results of the research data analysis, it was found that (1) Teacher activity in cycle I was 70.83% (good category), and increased in cycle II by 90.83% (very good category), (2) Student activity in cycle I was 66.67% are in (quite good category), and increased in cycle II by 87.50% (very good category), (3) Student learning outcomes in the first cycle are 73.08% in the good category, and increased in the second cycle amounted to 88.46% (very good category). Thus it can be concluded that the application of the Think Talk Write (TTW) Strategy in Indonesian language lessons in poetry material can increase teacher activity, student activity and improve learning outcomes in Indonesian language material in the theme of the Cita-Citaku theme and the sub-theme of Aku and Cita-Citaku for grade IV students. B UPT, SD Negeri 01 Limo Kaum.